Kesulitan Siswa dalam Menyelesaikan Soal Fisika pada Materi Suhu dan Kalor di Kelas X SMA Ar-Risalah Lubuklinggau Tahun Pelajaran 2016/2017 - Charli, Leo; Amin, Ahmad; Agustina, Desi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the types of difficulties, the causative factors, and provide solutions to overcome the difficulties in solving physics problems with temperature and heat matter. This type of research is a qualitative descriptive study, a sample of 30 students, taken by purposive sampling technique. Data collection techniques using tests, questionnaires, and interviews. The results of the analysis of the test data found the proportion of difficulties in understanding the questions that is equal to 80.3%, difficulty using symbols at 76.2%, difficulty using the formula at 84%, difficulty analyzing graphics at 65% and difficulty at counting at 90%. Based on the results of interviews and questionnaires, the factors causing students to have difficulty understanding the questions are students not understanding the purpose and objectives of the questions, lack of student understanding of the material, students rarely repeat the material that has been learned at home and students are lazy to practice working on the problems. The cause of difficulty using symbols is students forget about physics symbols and students remember symbols by memorizing instead of understanding them. The cause of difficulty using, because students are not interested and feel complicated with the problems contained in the formula, students do not master the material concepts well. The cause of difficulties in analyzing graphs is that students do not understand the purpose of the graph, students feel complicated and are not interested in the problems contained in the graph. The reason for arithmetic difficulties is that students are not interested in counting problems, students are not careful in calculating, students have difficulty doing arithmetic operations, and teachers rarely give varied problems. Conclusion, this problem can be overcome by frequently reading reference books, more diligent in doing the assignments given by the teacher, more active practice of physics problems at home, more concentrated when analyzing graphs and not in a hurry, students must often practice calculation problems so that the skills counting can increase. Keywords: Difficulty Analysis, Solving Problems, Temperature and Heat